Influência do processo da fabricação nas propriedades de filmes biodegradáveis a base de galactomanana - Nascimento, Jéssica Felipe do (2019)
The increase in the use of plastic packaging derived from non-renewable sources has motivated the development of biodegradable films or coatings in order to minimize the environmental impacts caused by indiscriminate disposal of synthetic polymers. In this context the galactomannan polysaccharide represents a good alternative of renewable raw material for the formation of biodegradable films. The present work had the objective of analyzing the potential of galactomannan from locust bean pods (Prosopis juliflora) in the process of manufacturing biodegradable films. For the preparation of the films different formulations of galactomannan 5% (m/v) were developed with the addition of 9% collagen and also glycerin in the proportion of 20% of the mixture. The raw materials and the films obtained were characterized using granulometric analysis, galactomannan yield, visual and tactile analysis, thickness, X-ray diffraction (XRD), Fourier Transform Infrared (FTIR), Ultraviolet-Visible Spectrophotometry Thermogravimetric analysis (TGA), Mechanical resistance, Scanning Electron Microscopy (SEM), Roughness and Contact Angle (AC). The formulations were applied as a cover to evaluate the conservation of post harvest strawberries. The results show that the methodology used for galactomannan extraction optimized the biodegradable film production process. The Spin coating deposition technique was the one that presented the best results when compared to those obtained by Casting. Among the formulations analyzed the films of formulation 1 presented properties with potential to replace the synthetic polymers. The increase in strawberry conservation time was achieved by using formulation 4 as cover.